Malignancy in contralateral thyroid lobe - Muhammad Naseem Baloch; Saad Abdul Razzak; Zahid Mehmood; Sana Naz; Sehrish Altaf; Arsalna Javed (Open Journal of Thyroid Research - Peertechz Publications, 2019)
Objective: The aim of this study was to evaluate tumour in contralateral thyroid lobe who underwent lobectomy and isthmusectomy for solitary thyroid nodule and proved malignant on histopathology and subsequently underwent completion thyroidectomy. Study Design: Cross sectional descriptive study Place and Duration of Study: This study was conducted in surgical ward 25, Jinnah post graduate medical centre, Karachi,Pakistan from1st January 2018 to 31st May 2019.